Diet Quality and Its Association with Cardiometabolic Risk Factors Vary by Hispanic and Latino Ethnic Background in the Hispanic Community Health Study/Study of Latinos. Issue 10 (7th September 2016) - Mattei, Josiemer; Sotres-Alvarez, Daniela; Daviglus, Martha L; Gallo, Linda C; Gellman, Marc; Hu, Frank B; Tucker, Katherine L; Willett, Walter C; Siega-Riz, Anna Maria; Van Horn, Linda; Kaplan, Robert C
Abstract: Background : Healthful diet quality has been associated with a lower risk of metabolic syndrome (MetS) in several populations, but reports on Hispanic and Latino cohorts, grouped or by ethnic background, have been limited and inconsistent. Objective: We aimed to examine diet quality by using the 2010 Alternate Healthy Eating Index [(AHEI) range: 0–110, lowest to highest quality] and its cross-sectional association with MetS and its cardiometabolic components across 6 Hispanic and Latino backgrounds. Methods: We studied 12, 406 US Hispanics and Latinos, aged 18–74 y and free of diabetes, from the multicenter, population-based Hispanic Community Health Study/Study of Latinos cohort. Food and nutrients were assessed from two 24-h recalls. MetS was defined by using the 2009 harmonized guidelines. Complex survey procedures were used in multivariable-adjusted linear regression models to test the association of the AHEI with continuous markers and in logistic regression models with MetS as an outcome. Results: The prevalence of MetS was 24.2%. Overall, Hispanics and Latinos had low scores for intakes of sugar-sweetened beverages and fruit juices, whole grains, and fruit and favorable scores for trans fats and nuts and legumes, according to AHEI criteria. Adjusted mean AHEI and its individual components differed by ethnic background ( P < 0.001), ranging from 43.0 for Puerto Ricans to 52.6 for Mexicans. Overall, adjusted odds (95% CIs) of having MetS were 22% (9%, 33%) lower for each 10-unit increase in AHEI. This association was modified by ethnic background ( P -interaction = 0.03), with significantly lower odds observed only for Mexicans (30%; 95% CIs: 13%, 44%) and Central Americans (42%; 95% CIs: 9%, 64%) for each 10-unit increase in AHEI. AHEI was inversely associated with waist circumference, blood pressure, and glucose among Mexicans and Puerto Ricans and with triglycerides among Mexicans only, and positively associated with HDL cholesterol among Puerto Ricans and Central Americans (all P < 0.05). Conclusions: Diet quality differed by Hispanic or Latino background. Although healthier diet quality was associated with lower odds of MetS in the overall Hispanic and Latino cohort, the association of AHEI and cardiometabolic factors varied by ethnic background. Nutrition-related research and interventions among ethnically diverse groups should consider individual ethnic backgrounds to optimally address diet quality and cardiometabolic health. This trial was registered at clinicaltrials.gov as NCT02060344.